2012
DOI: 10.1093/chemse/bjs053
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Further Medical and Health Research on High-Potency Sweeteners

Abstract: High-potency or artificial sweeteners have historically been considered inert compounds without physiological consequences other than taste sensations. However, recent data suggest that some of these sweeteners have biological effects that may impact human health. Furthermore, there are significant gaps in our current knowledge of the pharmacokinetics of these sweeteners, their potential for “sweetener–drug interactions” and their impact on appetite and body weight regulation. Nine research needs are described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 64 publications
0
24
0
1
Order By: Relevance
“…Recent evidence suggests that some NNSs may cross the blood brain barrier and interact with neurally-expressed sweet taste receptors in vivo [84]. It has been proposed that activation of these receptors by NNSs in nutrient-sensing brain regions may provide inaccurate feedback about extracellular glucose levels, which could in turn alter glucose homeostasis and intake [85]. …”
Section: Extra-oral Mechanismsmentioning
confidence: 99%
“…Recent evidence suggests that some NNSs may cross the blood brain barrier and interact with neurally-expressed sweet taste receptors in vivo [84]. It has been proposed that activation of these receptors by NNSs in nutrient-sensing brain regions may provide inaccurate feedback about extracellular glucose levels, which could in turn alter glucose homeostasis and intake [85]. …”
Section: Extra-oral Mechanismsmentioning
confidence: 99%
“…Sucralose is used as a food additive in more than 80 countries, and is present in over 4,000 products, including baked goods3456. However, several studies have shown that sucralose has metabolic effects that may negatively impact human health78910111213. In addition, it has been found that sucralose is not stable at high temperatures1415.…”
mentioning
confidence: 99%
“…This advantage is even more pronounced with edible taste strips since lower amounts of taste stimuli are required (Smutzer et al, 2013). Thus, post-ingestive activities of sucralose (Brown et al, 2009; Brown et al, 2012; Pepino et al, 2013), or metabolism of sucralose in the digestive tract (Schiffman, 2012) should be minimal, and should have little or no effect on taste preferences measured in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%